A gênese de um espaço profissional : a Escola Técnica de Comércio do Colégio Farroupilha de Porto Alegre/RS (1950-1983) - Silva, Eduardo Cristiano Hass da (2017)
This dissertation aims to investigate the education process of accounting technicians in Rio Grande do Sul, based on the study of Escola Técnica de Comércio (ETC) of Colégio Farroupilha de Porto Alegre/RS (1950-1983) focusing specifically on the collective biography of teachers who formed the first groups of accounting technicians of the school, as well as the social ties and careers of these teachers. The research showed that ETC Farroupilha has two well defined historical moments when seen from the constitution of its faculty. The first moment goes from the foundation of the institution in 1950 until the year 1972, when the school moves from downtown Porto Alegre to Três Figueiras district, when the modifications imposed by the reform of education estimated by the decree-law number 5.692 begin to be implanted, which made the accounting technician a second level qualification. The period afterwards extends from 1972 to 1983, the year in which the school is deactivated. The aforementioned decree brought a great change in the teachers professional profile, as until then, in parallel to the activity of professors, they would practice professions referring to the disciplines that were ministered, such as professions of lawyer, accountant, economist, engineer, geographer, physician and industrial chemist. From 1972 onwards, teachers who have become members of the teaching staff of the school are predominantly licensed, with no other professions. As the study is centered on teachers' careers and their ties of sociability, it was decided to work with the teachers who entered the school until the year 1972, resulting in 27 subjects. The questions that guided the development of the research were: who were the ETC Farroupilha teachers? What is their background? In what spaces did they work beyond the school? How did their professional career happen? How would they act as teachers of a commerce course? What are the social ties among these subjects? How was the bond maintained? The answers to these questions could be given from the prosopography methodology, which Database in the form of an electronic plan had the following variables: teacher's name, gender, date and place of birth, date of death, religion, nationality, civil status, and place of residence when entering the ETC, period of work and topics taught at the school, higher education diploma, place of higher education, diploma of technical education, place of technical education, extra course, name and profession of parents, name and occupation of spouses, name and occupation of children and professional career. The results showed a predominance of a male teaching staff (23 men and 4 women), of Brazilian nationality (although with cases of parents and grandparents who came from Germany), with higher education (only 2 subjects had only technical training), predominating bachelors in economics, civil engineering, history and geography. The analysis of the trajectories of the teachers, based on the methodology of networks, showed an existence of different ties of sociability, being them professional, friendship and kinship, used to keep the institution status. In addition, it was also shown that the social ties involved the students, mainly from indications for jobs, and the presence of school members at times such as births, marriages and deaths of family members, as well as owners and representatives of local companies.